Allograft and Patient Outcomes Between Indigenous and Nonindigenous Kidney Transplant Recipients. Issue 4 (April 2020) - Howson, Prue; Irish, Ashley B.; D'Orsogna, Lloyd; Chakera, Aron; Swaminathan, Ramyasuda; Perry, Gregory; De Santis, Dianne; Tolentino, Raelene; Wong, Germaine; Lim, Wai H.
Abstract : Background: Kidney transplant outcomes of indigenous Australians are poorer compared with nonindigenous Australians, but it is unknown whether the type of acute rejection differs between these patient groups or whether rejection mediates the effect between ethnicity, death-censored graft failure (DCGF), and death with a functioning graft (DWFG). Methods: Biopsy-proven acute rejection (BPAR) rates and types were compared between indigenous and nonindigenous recipients. The associations between ethnicity, BPAR, DCGF, and DWFG were examined using adjusted competing risk analyses, and mediation analysis was conducted to determine whether BPAR mediated the adverse effects between ethnicity and outcomes. Results: Fifty-seven (9.3%) of 616 patients who have received kidney-only transplants between 2000 and 2010 in Western Australia were indigenous. Compared with nonindigenous recipients, BPAR rates were higher in indigenous recipients (42 versus 74 episodes/100 recipients, P < 0.01), with an excess of antibody-mediated rejections. During a median follow-up of 8 years, indigenous recipients were more likely to experience BPAR, DCGF, and DWFG compared with nonindigenous recipients, with adjusted subdistribution hazard ratio of 1.94 (1.39-2.70), 1.53 (0.85-2.76; P = 0.159), and 2.14 (1.13-4.06; P = 0.020), respectively. Although 70% of the effect between ethnicity and DCGF was mediated by BPAR, no similar association was found for DWFG. Conclusions: Indigenous recipients experienced poorer allograft and patient outcomes compared with nonindigenous recipients, with BPAR an important determinant for DCGF. Future research identifying other risk factors and mediators associated with patient survival in indigenous recipients should be considered a priority. Abstract : Supplemental Digital Content is available in the text.